Cyberpark: an-IoT based automated parking management and monitoring system using RFID and ESP32 - Muhamad, Nur Amalina; Othman, Norhalida; Md Sin, Nor Diyana; Abdul Rahman, Noor Hasliza; Mohd Rodzi, Muhammad Iskandar (UiTM Cawangan Perlis, 2025)
The growing number of vehicles in urban and institutional areas has created significant challenges in parking space management. Traditional parking systems, which rely on manual processes, are often inefficient, time-consuming, and lack real-time information, leading to increased traffic congestion, fuel consumption, and user dissatisfaction. To address these issues, this paper presents Cyberpark, an IoT-based Automated Parking Management and Monitoring System that integrates smart technologies to improve parking operations, enhance user convenience, and increase infrastructure safety. Cyberpark utilizes RFID technology for secure and automated vehicle access, infrared (IR) sensors to detect parking slot occupancy, servo motors to control entry and exit gates, and a water sensor to detect flooding within the parking area. The system incorporates two microcontrollers: Arduino UNO for local control and ESP32 for wireless communication with the Adafruit IO cloud platform. Real-time data from all sensors is uploaded to the cloud, allowing for remote monitoring and status updates via an online dashboard. The development process involved circuit simulation using Proteus 8 Professional and functional testing through the Wokwi simulator. Hardware components were assembled on a custom PCB, and the software was developed using the Arduino IDE. Results showed effective system performance in automating gate operations, accurately monitoring parking slot status, and issuing timely alerts during flood conditions. The real-time dashboard allowed for seamless user interaction and remote oversight. Cyberpark demonstrates the feasibility of integrating low-cost, open-source hardware with cloud-based IoT platforms to create a scalable, user-friendly, and environmentally responsive smart parking solution. This system is suitable for deployment in campuses, shopping complexes, or residential areas. The project contributes to the development of smart city infrastructure by offering a reliable, efficient, and safe approach to modern parking management.